2015
DOI: 10.1136/vr.102518
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the accuracy of needle placement as used in diagnostic local analgesia of the maxillary nerve for investigation of trigeminally mediated headshaking in horses

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms Conclusions: A negative response to diagnostic local anaesthesia of the maxillary nerve does not 28 disprove facial dysaesthesia as the cause of headshaking in that horse as a false negative response 29 could arise due to failure to deposit local anaesthetic around the target area. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
7
1
Order By: Relevance
“…Surface landmark success rates (50%) were slightly higher when compared to those previously reported (40%) (Wilmink et al 2015). Both studies reported success rates for veterinary students performing the injections, however, study design differences make direct comparison difficult, notably the use of differing contrast medium volumes (0.5 mL in this study compared to 0.1 mL), and different outcome measures (direct hit and miss used in this study compared to a zonal system) (Wilmink et al 2015).…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Surface landmark success rates (50%) were slightly higher when compared to those previously reported (40%) (Wilmink et al 2015). Both studies reported success rates for veterinary students performing the injections, however, study design differences make direct comparison difficult, notably the use of differing contrast medium volumes (0.5 mL in this study compared to 0.1 mL), and different outcome measures (direct hit and miss used in this study compared to a zonal system) (Wilmink et al 2015).…”
Section: Discussioncontrasting
confidence: 63%
“…Both studies reported success rates for veterinary students performing the injections, however, study design differences make direct comparison difficult, notably the use of differing contrast medium volumes (0.5 mL in this study compared to 0.1 mL), and different outcome measures (direct hit and miss used in this study compared to a zonal system) (Wilmink et al 2015). Higher success rates of up to 80% have been seen with more experienced operators, when performing the surface landmark-guided technique (Bardell et al 2010;Wilmink et al 2015), however smaller volumes (0.25 mL and 0.1 mL) of methylene blue dye were used in these studies and successful injection was defined by dissection rather than three dimensional imaging (Bardell et al 2010).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…; Wilmink et al . ). Where few horses with idiopathic headshaking showed improvement on anaesthesia of the infraorbital nerve, the majority (13 out of 16 = 81%) showed complete or partial improvement after anaesthesia of the posterior ethmoidal branch of the maxillary nerve (Newton et al .…”
Section: Neuromodulation Of Trigeminal Nerve Branches In the Equine Headmentioning
confidence: 97%
“…Experience of the performer is very important in the success rates of local anaesthetic techniques, as was shown by Wilmink et al . () for the perineural block of the maxillary nerve. Although blind techniques used to be the gold standard, nowadays ultrasound‐guided techniques are quickly being adopted.…”
Section: Introductionmentioning
confidence: 99%